The Diploma Mill Trap - O'Neill, G. Patrick (Canadian Journal of Counselling and Psychotherapy, 2011)
Seeking a post-secondary education within our borders is normally safe, but once outside Canada, the rules change. You can no longer assume, for instance, that education is a clean, honourable enterprise that polices itself. Everyone is on their own, particularly when it comes to private institutions. And nowhere is this more so than in the United States. As a result, unsuspecting, foreign students are easy prey. They are easily tricked into believing that diploma mills are bona fide when in fact they are not. This article alerts counselors to the problem. It is hoped that they, in turn, will caution students seeking studies abroad.